China’s Petropolitics: Its Business and Diplomacy in the South China Sea - Adiputra Zulham , Cipto; Badaruddin, Muhammad (Journal of International Relations on Energy Affairs, 2020)
China faces the threat of oil scarcity which has prompted the country to seek alternative oil sources, one of the disputed South China Sea. This research will discuss the relationship between China's energy needs and efforts to control the South China Sea, describing China's policies (petropolitics) in three approaches, namely diplomacy, military (defense) and economy (business, investment and aid) and policy implementation to realize the interests of controlling oil resources in the South China Sea region. This research uses a descriptive-qualitative method to analyze comprehensively the policy documents and official statements of the Government of China and ASEAN countries and supported by literature studies. The results of this research indicate that of the three approaches, the economic approach such as business and investment by China in Southeast Asia is currently more effective for China to strengthen its position and influence in Southeast Asia and the SCS dispute area and to control the oil in it. Meanwhile, diplomacy and military (defense) approaches use to support this economic approach.